THE EFFECT OF THE TEMPERATURE AND FRYING TIME ON THE QUALITY OF SPICE SHREDDED FISH OF LITTLE TUNA (Euthynnus affinis) - Muliawati, Meity; Mus, Sukirno; Buchari, Dewita (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
has been conducted in April 2016. The aim of this study was to know the effect oftemperature and frying time and it’s interaction to produce the best quality of theshredded fish. The method of this study was an experiment method, that usingtemperature and different frying time. The quality parameter used theorganoleptic analysis (colour, smell, taste and texture) and the proximate (water,protein, fat and ashes). The analysis of variance (Completely RandomizedDesign/CRD) has been used to set the evaluation of the research, with factorialthat consist of temperature 1000C-1150C (S1), 1100C-1250C (S2), 1200C-1350C(S3) as the first factor and the frying time is 7,5 minutes (W1), 8 minutes (W2), 8,5minutes (W3) as the second factor. The result of this study showed that the bestquality of the shredded Little Tuna was S3W3 (1200C-1350C, 8,5 minutes), such asyellowish-brown, very specific and special smell, very delicious and very tasty,soft and crispy. The content of water was 9,65, content of protein was 39,45%,content of fat was 25,47% and content of ashes was 8,2%.Key word : shredded, little tuna, temperature and time.